Evaluación de riesgo y análisis de la vulnerabilidad ante amenazas de inundación en el Centro Poblado Huancaquito Bajo, Distrito de Virú, Provincia de Virú, 2018 - Espire Gil, Ronald Milton (2019)
In this research presents the study of risk evaluation and analysis of vulnerability to flood threats in the populated center Huancaquito Bajo. The populated center is located on the left margin of the Virú River and during periods of the phenomenon of the child floods of large agricultural and urban areas occurred according to the data presented by the National Institute of Civil Defense (INDECI, by its Spanish acronym) That is why we searched to evaluate the risk and vulnerability analysis. Previous studies were necessary, such as the 2 km topographic survey of the populated center Huancaquito Bajo, the soil survey every 500 m and a hydrological study taking historical data from the Huacapongo and Sifón Viru hydrometric station, these basic studies allowed a hydraulic simulation to be carried out systematically, integrating technological tools such as the Hec-Ras 5.0.6, which allows modeling and hydraulic analysis, evaluating maximum flood flows at different return periods. Flow propagation results in flood zones. In addition, through the methodology for risk assessment imposed by the National Center for Estimation, Prevention and Reduction of Disaster Risk (CENEPRED, by its Spanish acronym) levels of danger and vulnerability were determined The results of extraordinary flows for return periods of 11, 73, 174, 225 and 475 years are 128.02, 308.99, 428.58, 469.26 and 602.83 m3 / s. Flood zones, maximum strains of 2.63m, flow rate less than 1.5m / s in urban areas, plus the Froude number at the analysis point is below 1, so the regime is subcritical. These data allowed to identify high level hazards, analyze the vulnerability that gave a percentage of 74.11% and evaluate the risk and establish it in a high stratum.